Electrochemical studies of the oxidation and reduction of dicobalta-superphane complexes - Trupia, Sabrina; Claßen, Jörg; Gleiter, Rolf; Geiger, William E. (Inorganica chimica acta, 2011)
The electrochemical oxidation of a series of dicobalta-superphanes has been studied. Complexes in which the redox centers are connected by four propano-bridges display two one-electron oxidations, at least one of them being reversible, at potentials close to that of the ferrocene oxidation. The potential separation of the successive anodic processes is suggestive of strong transannular electronic interactions between the two redox sites. Two complexes (6 and 7) having one or both of their cyclopentadienyl caps substituted with a methyl ester, and containing two ethano-bridges and two 1,3-disilapropano-bridges, have been similarly studied and the IR spectra of their oxidation products recorded. The monocation 7+ displays two IR-active νCO bands, indicative of trapped valency, but both bands are shifted from the energies observed for the fully oxidized or reduced redox sites. Combined with the large ΔE1/2 value for separation of the two one-electron oxidations of 7, the data are taken to denote a spin-localized but charge-delocalized model of the mixed valence state. Approximately 20% of the positive charge is transferred to the “unoxidized” side of the monocation 7+. Electrochemical data are also presented on the reductions of cobalt and dicobalta-superphanes having cyclobutadienone moieties linked by propano-bridges.
Gesehen am 17.11.2022
Dedicated to Prof. Wolfgang Kaim, in appreciation of his outstanding contributions to the understanding of redox properties of transition metal and organometallic complexes